Neurocognitive function across different phases of bipolar disorder: an evaluation using the B-CATS - Tian, Lu; Liu, Yi; Xu, Jinjie; Mao, Zhen; Xing, Xiaomeng; Bo, Qijing; Hu, Chen (Frontiers in Psychiatry, 2025)
ObjectivesNeurocognitive dysfunction is a critical aspect of bipolar disorder (BD) and affected by multiple factors, which may serve as potential points for prevention and clinical intervention. This study aimed to compare the neurocognitive profiles of BD patients across different phases with those of healthy controls (HCs) via the Brief Cognitive Assessment Tool for Schizophrenia (B-CATS) and explore the relationship between neurocognitive impairment and mood symptom severity, advancing the applicability of the B-CATS for BD patients.MethodsThis cross-sectional study included 238 BD patients, of whom 80, 78, and 80 were in the depressive, manic/hypomanic, and euthymic phases, respectively, and 80 HCs. The participants’ neurocognitive profiles were evaluated using the B-CATS, which includes 3 tests: the Animal Fluency Test (AFT), the Digit Symbol Substitution Test (DSST), and the Trail Making Test (TMT). In addition, the 17-item Hamilton Depression Rating Scale (HAMD-17), Hamilton Anxiety Rating Scale (HAMA), Young Mania Rating Scale (YMRS) and Sheehan Disability Scale (SDS) were used to assess depression symptoms, anxiety, mania, and the degree of disability.ResultsAmong the four groups, the depressive group showed the most severe neurocognitive impairment, followed by the manic group, and the euthymic group was inferior to that of the healthy control group (p < 0.001). Correlation analysis showed that in the depression group, depressive symptoms were inversely associated with AFT (r = -0.427, p < 0.001), DSST (r = -0.242, p = 0.030), and total scores (r = -0.248, p = 0.026). In the manic group, manic symptoms were inversely associated with B-CATS scores (r = -0.407, p < 0.001), and patients with current medication use had lower B-CATS total scores and TMT scores (r = -0.310, p = 0.006; r = -0.292, p = 0.010, respectively). Multiple regression analysis showed that B-CATS total score was closely related to SDS- Social life (p = 0.030) in depression, YMRS score (p < 0.001) and drugs (p < 0.001) in manic.ConclusionsNeurocognitive impairment in BD patients are present throughout the entire illness course, with the most severe deficits occurring during the depressive phase. B-CATS is a quick and simple tool for assessing neurocognitive function for BD patients.